An Extensive Review of Health and Economy of Bangladesh Amid Covid-19 Pandemic - Abdul Kader Mohiuddin; Muhammad Ridwan (Budapest International Research and Critics University, 2020)
COVID-19 has affected 213 countries around the world, killing 711,313 and infecting around 19 million by August 06, 2020 (worldometer.info). Bangladesh, a South Asian low-middle-income economy, has experienced a demographic and epidemiological transition with rapid urbanization and a gradual increase in life expectancy. It is the seventh most populous country in the world and population of the country is expected to be nearly double by 2050. The increasing burden of communicable diseases in Bangladesh can be attributable to rapid urbanization and nearly 50% of all slum dwellers of the country live in Dhaka division. In 2017, National Rapid Response Team of IEDCR investigated 26 incidents of disease outbreak. Until August 6th, death reported 3,267 and 246,674 got infected in this country. The joint survey of the Power and Participation Research Centre and BRAC Institute of Governance and Development reveals that per capita daily income of urban slum and rural poor drops by 80% due to present countrywide shutdown enforced by the government to halt the spread of Covid-19. 40%-50% of these population took loans to meet the daily expenses. However, the country has just 127,000 hospital beds, 91,000 of them in government-run hospitals. Researchers say, the country’s economy is losing BDT 33 billion every day from its service and agriculture sectors during the nationwide shutdown.